(untitled) (Research, Society and Development, 2025)
This review addresses the psychological effects of the COVID-19 pandemic, with an emphasis on anxiety and depression disorders. In this context, the research highlights that the pandemic generated a significant increase in stress, resulting in higher levels of anxiety and depression in the Brazilian population. Objectives: based on a systematic literature review, the study aims to analyze existing evidence on how the pandemic affected mental health, identifying factors associated with the increase in these disorders. The authors discuss the prevalence of symptoms of anxiety and depression, as well as the impact of social isolation, financial difficulties, and grief, which intensified these conditions. Methodology: the research includes a rigorous methodology, considering criteria for inclusion and exclusion of studies, and uses recognized databases to ensure the quality of the evidence. Results: the results of this systematic review aim to contribute to the understanding of the impact of the pandemic on mental health, providing support for the formulation of new strategies for managing mental disorders within the context of the Brazilian Unified Health System (SUS). In addition, the work intends to serve as a reference source for future studies in the field of mental health, with the purpose of improving the diagnosis and treatment of psychological conditions exacerbated by the health crisis.